Behavior of suprathermal electrons at the Uragan-3M torsatron after RF heating off - Zamanov, N.V.; Pavlichenko, R.O.; Kulaga, A.E. (Вопросы атомной науки и техники, 2016)
For the past decades the microwave radiometry is a routinely used diagnostics to obtain the information on temporal evolution and radial profile of the bulk electron temperature at Uragan-3M torsatron plasma experiments. However, in the case of low plasma density operation we observe the high level of electron cyclotron emission at the frequencies that match the second and third harmonics of the extraordinary mode after RF heating pulse off. This effect could be explained with the production of the suprathermal electrons. Study of the behavior suprathermal electrons is of great importance because: (a) suprathermal electrons significantly distort or make it impossible to measure the thermal electron temperature; (b) such electrons influence the ionization process, the excitation of the plasma ions and may lead to the occurrence of several plasma instabilities. The present work describes the results of experimental studies of the behavior of the emission after turning off the RF heat pulse